Contemporary monster theory: How monsters promote kindness and allyship in picturebooks - Jana R. Zeilinga; David E. Robinson; Christopher W. Koekemoer (Literator, 2025)
Children’s picturebooks can significantly influence how young readers perceive the world around them. Despite the common perception of childhood as a time of innocence and fragility, themes involving fear, monsters, and frightening scenarios are surprisingly widespread in literature for young audiences. Drawing on recent developments in contemporary monster theory, this study explores the meaningful and symbolic presence of monsters in Western society. These figures function as cultural constructs that help define social boundaries – clarifying who belongs and who is marginalised as ‘monstrous’. This research involved a surface reading and broad analysis of eight picturebooks by three different authors to examine how monsters are portrayed in children’s literature and what roles they serve. The findings reveal that monsters are frequently depicted as sympathetic beings who seek love and acceptance. Their portrayals offer young readers accessible models of inclusion, such as practicing kindness and allyship. Ultimately, the study shows that monsters in the selected picturebooks challenge rigid ideas of normalcy, encouraging children to embrace diversity rather than fear it.